2019
DOI: 10.1111/1759-7714.13193
|View full text |Cite
|
Sign up to set email alerts
|

Post‐progression survival is highly linked to overall survival in patients with non‐small‐cell lung cancer harboring sensitiveEGFRmutations treated with first‐line epidermal growth factor receptor‐tyrosine kinase inhibitors

Abstract: BackgroundIn patients with epidermal growth factor receptor (EGFR)‐mutated advanced non‐small‐cell lung cancer (NSCLC), epidermal growth factor receptor‐tyrosine kinase inhibitor (EGFR‐TKI) treatment has shown a good response. Subsequent treatments jeopardize the ability to determine the effect of first‐line chemotherapy on overall survival (OS). Therefore, using patient‐level data, we aimed to study the associations of progression‐free survival (PFS) and post‐progression survival (PPS) with OS after first‐lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The relationship between subsequent treatment after disease progression and OS is intriguing, and previous studies of patient-level data have identified a strong relationship between PPS and OS following first-line treatment for patients with advanced NSCLC or extensivestage small cell lung cancer [12][13][14][15]. However, the correlation between PPS and OS is unclear among patients with high-programmed death-ligand 1 (PD-L1) expression undergoing first-line pembrolizumab monotherapy for NSCLC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between subsequent treatment after disease progression and OS is intriguing, and previous studies of patient-level data have identified a strong relationship between PPS and OS following first-line treatment for patients with advanced NSCLC or extensivestage small cell lung cancer [12][13][14][15]. However, the correlation between PPS and OS is unclear among patients with high-programmed death-ligand 1 (PD-L1) expression undergoing first-line pembrolizumab monotherapy for NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, pembrolizumab monotherapy is now considered a standard firstline treatment for patients with high PD-L1 expression and no contraindications to immune checkpoint inhibitors. Unfortunately, there are limited patient-level data regarding PPS in this setting [12,15]. Therefore, this study aimed to evaluate the patient-level correlations of PFS and PPS with OS among patients undergoing firstline pembrolizumab monotherapy for advanced NSCLC and how subsequent treatments influence PPS.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies in patients with NSCLC have also demonstrated that PPS is highly correlated with OS beyond first-, second-, or third-line therapy [ 7 , 8 , 39 ]. Moreover, our previous studies revealed that patient-level data on PPS are relevant for evaluating early (first- and second-line) therapies in patients with advanced or metastatic NSCLC, as well as first-line treatment in patients with extensive-disease SCLC [ 10 , 40 , 41 , 42 , 43 ]. Therefore, in this study, we analyzed RFS and PPS in patients with postoperative relapse of EGFR -mutated NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that PPS has a stronger significance on OS than PFS in patients with NSCLC harboring sensitizing epidermal growth factor receptor ( EGFR ) mutations treated with first-line EGFR-TKIs. This means that treatment beyond disease progression after front-line treatment may have a significant influence on the OS of patients with NSCLC [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Along with the new emerging checkpoint inhibitors in lung cancer, it is expected that increasing the overall survival rate in lung cancer will involve detecting particular targetable gene mutations and PD-1/PD-L1 expression. EGFR mutations are linked with good prognosis in lung cancer patients mainly attributed to the treatment of tyrosine kinase inhibitor (TKI) [ 12 ], but also seen in surgically resected non-small cell lung cancer (NSCLC) without receiving TKI [ 13 ]. Several reports have also shown association between the expression of PD-L1 and poor survival rate in lung cancer patients [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%